Weather variability and energy demand: an applied study of daily temperatures in the Iraqi capital, Baghdad - ميثم ربيع هادي الحسناوي (Iraqi Journal for Administrative Sciences, 2025)
It has become climate change as one of the most powerful speeches and conversations in the world. The rise in temperatures ascribed to the rising levels of carbon oxides has led and will lead to increasing diversified combination of negative effects, economically, socially, politically, and biology. As much as $2 trillions dollar of the U.S. economy is weather sensitive and same case applies to the British economy as the UK Meteorological Office indicates that as many as (70%) of UK firms are affected by the weather. Browsing any specialized financial newspaper is sufficed to uncover a long list of companies blaming their losses on the weather. The volatile weather conditions impact on the quantities (as well as prices) of energy required, combined this with a lot of uncertainty about future market conditions cast a heavy shadow on energy users and producers alike. Therefore, this research seeks to demonstrate the characteristics of temperatures in Iraq (represented by Baghdad, the capital) and see its effect on the demand for energy (represented by the consumption of crude oil). This research based on number of hypothesis, including that the temperature has a tendency of average reverting and they tend to fall in the summer and the rise in winter, and this means that there is a tendency for a potential downward in the need for cooling and heating, and thus in the demand for energy in the future. By using a set of mathematical, statistical and financial methods, this research has reached to number of conclusions, all rejected the research\'s hypotheses and it has reached also to number of recommendations including the following: 1. Iraq should use the weather international markets to deal with the threats and challenges of weather volatility risk and hedge their negative effects on the demand for various energy products. Along with traditional risk management solutions, weather derivatives can now protect energy revenues from anticipated drops in demand. Needless to say, predictability and stability of cash flows are of crucial importance for energy sector. Because weather hedging can stabilize revenues, it is possible to set up renewable energy projects with the contribution of a private sector because it can use them to produce the stable and predictable results investors and lenders from the private sector appreciate, all of which contribute to supporting and enhancing Iraq\'s energy and diversify the sources of budget revenues and activate a private sector activity. 2. The variation in the need for heating and cooling in Iraq and their tendency to decline on the monthly, seasonally and annually levels may led, from one side, to drop in demand for energy in the future in Iraq and draws attention, from the other side, that the global demand for energy is likely to fall due to volatile weather. Therefore, the economic policy maker should insert a very important weather factor in the equation estimating the expected demand for Iraqi crude oil in the coming years because of its direct impact on the expected oil revenues especially with fact that Iraq\'s economy and its budget is absolutely dependent on these revenues.